DISPENSASI PERKAWINAN PERSPEKTIF PERLINDUNGAN ANAK - Ali Imron (Fakultas Hukum Universitas Wahid Hasyim, 2011)
People who will conduct a marriage should fulfill administrative and substantiverequirements. These marriage requirements have positive roles in theachievement of goal and meaning of a marriage for the involved parties. Amarriage is permitted if the male party has come to the age of 19 and the femaleparty has come to the age of 16. However, a marriage dispensation proposal maybe proposed by the parties with various reasons. This will open the chanche of theoccurrence of under-aged marriages. A marriage dispensation should be basedon the consideration of the benefits for children and family. Even those benefits forchildren should be put on the priority above their parents and extended family`simportance as the realization of child protection. Parents should prevent theoccurrence of marriages in minor ages for the realization of qualified, decent, andprosperous Indonesian children.Key Words: Marriage, Dispensation, Child Protection